PENETAPAN MODEL BANGKITAN PERGERAKAN UNTUK BEBERAPA TIPE PERUMAHAN DI KOTA PEMATANGSIANTAR - Muhammad Efrizal Lubis; Novdin M Sianturi (Media Teknik Sipil, 2012)
Town expansion not followed by infrastructure development can result many problems andone of them is related to transportation. This research aims to model Trip generation conducted bysome community of housing types in Pematangsiantar town. And the research of this is done toknow and estimate the level of out movement from the housing that will be used for forecasting inorder to overcome all problems at the future period.The primary survey is done by filling thequestionnaire by 86 members of families which are living in three housing type’s area that is luxurious,middle and simple. The result of the questionnaires will be tabulated to become dependent variableand independent variable. Moreover, it will be analyzed by SPSS-12 program. The equation regressionof it will be used to model and awaken the trip of community in some housing types in Pematangsiantartown.From the final result model test, it was gotten that the trip generation in three housing typearea that is luxurious housing type (Y1), middle housing type (Y2), and type housing of simplebuilding (Y3) had been very influenced by amount of family member (X1), amount of the ownershipof car (X3), amount of the ownership of motorcycle (X4) and amount of family go to school (X6).The regression model equations are included by luxurious housing type (Y1) = -0,728 + 1,885 X1+ 0,649 X3 + 0,772 X6, middle housing type (Y2) = 0,600 + 1,300 X1 + 0,900 X3, simple housingtype (Y3) = 0,271 + 1,518 X1 + 0,905 X4.Keyword: Trip generation model, Housing typologies.